Application of Concrete Pros in Improving Science Learning Results Simple Electricity Circuit Material at Elementary School - Hartono, Rudi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to motivate and improve student achievement in grade VI SD Negeri Malahayu 03 in learning science about simple electrical circuits. The low evaluation results are usually related to student behavior during learning. For example, students often go in and out of class alternately, talk to themselves, and do not dare to ask questions to the teacher when they have difficulties. To achieve success in learning in a class, it is necessary to use appropriate learning methods and use of teaching aids. Teaching aids that encourage students to be active in the learning process of Natural Sciences are concrete teaching aids. Based on the data of grade VI students of SD Negeri  Malahayu 03 who achieved the Minimum Completeness Criteria, from 44 students there were 19 students (43%) in the pre-cycle to 31 students (71%) in the first cycle and 40 students (100%) in the second cycle. The conclusion of this study shows that learning with concrete media can improve science learning outcomes for grade VI students of SD Negeri Malahayu 03, Banjarharjo District, Brebes Regency in the first semester of the 2019/2020 school year.